Concentrations and Radiation Hazard Indices of Naturally Radioactive Materials for Flour Samples in Baghdad Markets (Baghdad Science Journal, 2021)
In the present work, Uranium (238U), Thorium (232Th) and Potassium (40K) specific activity concentration in (Bq/kg) was measured in five different types for wheat flours that are available in the Iraqi markets. The gamma spectrometry method with an NaI (Tl) detector has been used for radiometric measurements. Calculations of radium equivalent activity, annual effective dose equivalent, external hazard index (Hex), internal hazard index (Hin), representing gamma index and gamma dose rate in all  flour samples were 17.98132 Bq/kg, 0.0100334, 0.04502, 0.04857, 0.06872, 0.125883 and 8.181244 respectively. It is found that the average of specific activity concentration of wheat flour samples for 238U, 232Th and 40K are 7.4564 Bq / kg, 6.27962 Bq / kg and 20.0658 Bq / kg respectively. This study proves that the natural radioactivity and radiation hazard indices were lower than the safe.    Measurements of hazard indices show that the concentrations of these isotopes in all samples are within the allowable limits internationally.    The Radium Equivalent Activity, Annual Effective Dose Equivalent, External hazard index (Hex), Internal hazard index   (Hin), represented Gamma Index and Gamma Dose Rate are also calculated. All data were measured at the March of 2019.